Statistical strained-tetrahedron model of local ternary zinc blende crystal structures - Robouch, B.V.; Sheregii, E.M.; Kisiel, A. (Физика низких температур, 2004)
The statistical strained-tetrahedron model was developed to overcome two common assumptions
of previous models: 1) rigid undistorted ion sublattice of regular tetrahedra throughout all
five configurations and 2) random ion distribution. These simplifying assumptions restrict the
range of applicability of the models to a narrow subset of ternary alloys for which the constituent
binaries have their lattice constants and standard molar enthalpies of formation (∆fH₀) equal or
quasi-equal. Beyond these limits predictions of such models become unreliable, in particular, when
the ternary exhibits site occupation preferences. The strained-tetrahedron model, free from rigidity
and stochastic limitations, was developed to better describe and understand the local structure
of ternary zinc blende crystals, and interpret experimental EXAFS and far-IR spectra. It considers
five tetrahedron configurations with the shape and size distortions characteristic of ternary zinc
blende alloys, allows nonrandom distributions and, hence, site occupation preferences, conserves
coordination numbers, respects stoichiometry, and assumes that next-neighbor values determine
preferences beyond next-neighbor. The configuration probabilities have three degrees of freedom.
The nineteen inter-ion crystal distances are constrained by tetrahedron structures; to avoid destructive
stresses, we assume that the average tetrahedron volumes of both sublattices relax to
equal values. The number of distance free-parameters ≤ 7. Model estimates, compared to published
EXAFS results, validate the model. Knowing the configuration probabilities, one writes the dielectric
function for far-infrared absorption or reflection spectra. Constraining assumptions restrict
the number of degrees of freedom. Deconvolution of the experimental spectra yields site-occupation-
preference coefficient values and/or specific oscillator strengths. Validation again
confirms the model.